miR-221/222-3p act as potential circulating factors in heart failure to stimulate cancer progression - Xu, Rongfeng; Guo, Jiaqi; Ji, Zhenjun; Zhu, Kongbo; Sheng, Zulong; Zuo, Pengfei; Carvalho, Abdlay; Yao, Yuyu; Ma, Genshan; Zhang, Rui (Frontiers in Oncology, 2026)
BackgroundRecent epidemiological studies have shown that heart failure (HF) can lead to an increased incidence of cancer. However, there is limited information regarding how HF promotes cancer development. We attempted to clarify the potential role of miR-221/222-3p dysregulation in HF in promoting cancer through comprehensive application of various bioinformatics tools and in vitro validation.MethodsVarious bioinformatics tools, including TargetScanHuman, the Human microRNA (miRNA) tissue atlas, RNA structure, miRNET, DAVID, Enrichr, FunRich, STRING, MalaCards, miRcancer, OncoLnc, miRTargetLink, GEPIA, the cBioportal, the GEO database, and Cytoscape, were comprehensively applied. Twenty patients with coronary artery disease (CAD) admitted to Zhongda Hospital, Southeast University, were enrolled in this study. The patients were divided into HF and non-HF groups. Serum (5% in complete medium) from patients with or without HF was added to the HT-29 cell culture medium. Inhibitors of miR-221/222-3p were constructed. EdU kits and CCK8 kits were used for proliferation detection. Western blotting was used to measure the level of PCNA. qRT-PCR was used to measure the levels of miR-221/222-3p.ResultsmiR-221/222-3p was widely distributed in various tissues and organs, including the heart. The PPI network revealed that miR-221/222-3p was closely associated with HF, whereas the KEGG pathway analysis indicated that the functions of miR-221/222-3p were mainly cancer-related. The Cytoscape analysis indicated that miR-221/222-3p act as key regulators of the progression of several common malignant tumors through their target mRNAs. In vitro experiments showed that miR-221/222-3p was elevated in the serum of HF patients and in human colon cancer cells (HT-29) treated with HF serum. HF serum promoted the proliferation of HT-29 cells, which was reversed by miR-221/222-3p inhibitors.ConclusionmiR-221/222-3p may be an important link between HF and cancer, as they are upregulated in HF and thus promote cancer.